Management of Congenital Talipes Equino Varus (CTEV) by Ponseti Casting Technique in Neonates: Our Experience - Saif Ullah, Md.; Ferdous, Kazi Md. Noor-ul; Shahjahan, Md.; Abu Sayed, Sk. (Journal of Neonatal Surgery, 2013)
Objective: The purpose of this study is to evaluate the results of Ponseti technique in the management of congenital Talipes Equino Varus (CTEV) in neonatal age group. Methods: It is a prospective observational study, conducted during the period of July 2010 to December 2011 at the Department of Pediatric Surgery in a tertiary hospital. All the neonates with CTEV were treated with Ponseti casting technique. Neonates with other congenital deformities, arthrogryposis and myelomeningocele were excluded. Results: Total 58 CTEV feet of 38 neonates were treated. Twenty six were males and 12 were females. Thirty seven (63.8%) feet were of rigid variety and 21(36.2 %) feet were of non-rigid variety. Twenty patients had bilateral and 18 had unilateral involvement. Mean pre-treatment Pirani score of study group was 5.57. Mean number of plaster casts required per CTEV was 3.75 (range: 2-6). Thirty five rigid and 15 non-rigid (total 86.2%) feet required percutaneous tenotomy. Out of 58 feet 56 (96.6%) were managed successfully. Three (5.2%) patients developed complications like skin excoriation and blister formation. Mean post-treatment Pirani score of the study group was: 0.36 ± 0.43. Conclusion: The Ponseti technique is an excellent, simple, effective, minimally invasive, and inexpensive procedure for the treatment CTEV deformity. Ideally it can be performed as a day case procedure without general anesthesia even in neonatal period.